Employment Outcomes and Career Progression of BSIT Graduates at Isabela State University – Roxas Campus - D. Alzate, Ma. Valen; Laurel, Jay E. (Universitas Negeri Padang, 2025)
Graduate tracer studies serve as a vital tool for assessing the relevance and impact of higher education on graduates' career outcomes. This study examines the employment status, career progression, and curricular relevance of Bachelor of Science in Information Technology (BSIT) graduates from Isabela State University – Roxas Campus. Using a descriptive research design, data were collected from 288 graduates (2009–2024) through an online structured survey. Findings reveal that 69.79% of graduates are employed full-time, while 13.19% remain unemployed. However, only 31.94% have received job promotions, and 23.00% pursued further studies, indicating challenges in long-term career advancement. Graduates highlighted the need for curriculum enhancements, including industry-based training, advanced programming, and cybersecurity integration. The study underscores the importance of strengthening industry-academe collaboration, aligning curricula with industry demands, and fostering lifelong learning to enhance graduates’ career trajectories in the evolving ICT landscape.